Jeddah Islamic Port: Strategies for Responding to the Probable Economic Shocks of 2020-2030 - Abosuliman, Shougi Suliman (Journal of King Abdulaziz University: Marine Sciences, 2022)
Jeddah is the sea gateway to the commercial heart of Saudi Arabia, and there are high expectations from the port to significantly increase its contribution to non-oil gross domestic product. However, the geopolitical issues between the United States of America and China intruded, then the COVID-19 pandemic which will significantly impact global trade. This study investigates the effects of these conditions and rising port competition on government policy (Vision 2030) for Jeddah Islamic Port. Interviewing key respondents in the public and private domains, this research fleshes out statistical measures, and critically reviews information from many sources to establish the ongoing status of Jeddah Islamic Port. Significant bottlenecks in landside logistics, such as road and storage facilities are currently being addressed. Current digitisation advances have been adopted in a supply chain logistics platform focussed on the port, and with plans for container loading-unloading and on-site storage automation. Sustainability is viewed by Mawani (i.e., port authority) as meeting international protocols on emissions and waste. However, the rise of mega-container ships, the enhanced Suez Canal traffic, and the dominance of Chinese shipping put pressure on the port administrators to engage with their port tenants and with foreign ports to ensure that Jeddah Islamic Port remains a key player in global trade. Inter-port communications are found to be a critical trade practice in the face of emerging competitions in the region.